Endodontical treatment of periapical tooth injury with photodynamic therapy: Case report - Lopes, Camila Soares [UNESP]; Moreira, Suellen de Azevedo; Nicoli, Giovanni Antonio; Ramirez, Iago; Viola, Naiana Viana (Elsevier B.V., 2019)
This article describes the use of Photodynamic Therapy (PDT) during the endodontic treatment of teeth with periapical lesion. Patients presented tooth 35 with diagnostic hypotheses of Periapical Cyst or Granuloma. The Crown-Down preparation was performed with the HyFlex CM system. In case I it was not possible to reach the working length, in case II the foraminal debridement was performed at the actual tooth length. In the final irrigation, the E1 - Irrisonic ultrasonic insert was used, promoting sequentially agitation of NaOCl 2.5%, EDTA 17% and NaOCl 2.5%. Then, PDT was applied with 0.005% methylene blue dye. Calcium Hydroxide with Parammonochlorophenol was used and after 15 days, the final irrigation protocol and PDT were performed again. After 90 days of case I and 1 year of case II, the total lesion regression was observed in both cases. It is concluded that the proposed treatment improved the microbial disinfection favoring the regression of the periapical alterations providing satisfactory clinical and radiographic results.
Keywords: Antimicrobial photodynamic therapy; Biofilm; Endodontics